2022
DOI: 10.1186/s12889-022-14421-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the rural–urban disparity in acute respiratory infection symptoms among under-five children in Sub-Saharan Africa: a multivariate decomposition analysis

Abstract: Background Acute Respiratory Infections (ARIs) account for more than 6% of the worldwide disease burden in children under the age of five, with the majority occurring in Sub-Saharan Africa. Rural children are more vulnerable to and disproportionately affected by ARIs. As a result, we examined the rural–urban disparity in the prevalence of ARI symptoms and associated factors among children under the age of five in Sub-Saharan Africa. Methods We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
1
3
1
Order By: Relevance
“…At the national level, the prevalence of ARI seems to be trending downward over the past 20 years: 12.0% in 2001, 9.5% in 2006 and 2.6% in 2014 47 48 57. According to the latest estimates, the percentage of ARI among children under 5 years in sub-Saharan Africa (8.6%) was higher than what we found 69. In the West African subregion, the prevalence of ARI in children under 5 years was: 1.1% in Togo (2017),66 2% in Sierra Leone (2019),59 2.1% in Guinea (2018),70 2.0% in Mali (2018),65 2.6% in Nigeria (2018),61 3.6% in Ghana (2014),60 4.4% in Liberia (2019–2020),64 4.6% in Gambia (2019–2020)67 and 5.0% in Senegal (2019) 62.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…At the national level, the prevalence of ARI seems to be trending downward over the past 20 years: 12.0% in 2001, 9.5% in 2006 and 2.6% in 2014 47 48 57. According to the latest estimates, the percentage of ARI among children under 5 years in sub-Saharan Africa (8.6%) was higher than what we found 69. In the West African subregion, the prevalence of ARI in children under 5 years was: 1.1% in Togo (2017),66 2% in Sierra Leone (2019),59 2.1% in Guinea (2018),70 2.0% in Mali (2018),65 2.6% in Nigeria (2018),61 3.6% in Ghana (2014),60 4.4% in Liberia (2019–2020),64 4.6% in Gambia (2019–2020)67 and 5.0% in Senegal (2019) 62.…”
Section: Discussioncontrasting
confidence: 83%
“…47 48 57 According to the latest estimates, the percentage of ARI among children under 5 years in sub-Saharan Africa (8.6%) was higher than what we found. 69 In the West African subregion, the prevalence of ARI in children under 5 years was: 1.1% in Togo (2017), 66 2% in Sierra Leone (2019), 59 2.1% in Guinea (2018), 70 2.0% in Mali (2018), 65 2.6% in Nigeria (2018), 61 3.6% in Ghana (2014), 60 4.4% in Liberia (2019–2020), 64 4.6% in Gambia (2019–2020) 67 and 5.0% in Senegal (2019). 62 In Indonesia, 4.2% of children under 5 years suffer from ARI in a study in 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Children who had diarrhea recently were more likely to develop ARI than those who did not have diarrhea. This study is supported by a previous study conducted in Ethiopia [20,35]. This is because children with concomitant illnesses such as diarrhea may have lowered immunity, making them more vulnerable to diseases such as ARI [20,38,39].…”
Section: Discussionsupporting
confidence: 73%
“…The higher risk of ARI among younger children might be due to their less developed immunity [20,34]. In contrast, other studies have suggested that children older than 36 months are less likely to develop ARI [33,35].…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to rural areas, where the number of positive patients was 1.2 times higher than the number of negative patients, urban environments corresponded to approximately 1.6 times more positive patients than negative patients. This result suggests that urban areas may have greater rates of infectious transmission [38]. From an environmental standpoint, metropolitan areas have a higher rate of mutation development than rural ones, which determines the body's increased production of IgE [39].…”
Section: Environment Corellated With Elevated Ige Levelsmentioning
confidence: 99%